HUBUNGAN NILAI KEBENARAN BERDASARKAN FILSAFAT ILMU DENGAN TINDAK KEKERASAN SEKSUAL TERHADAP PEREMPUAN - Tenripadang, Andi (AL-MAIYYAH, 2016)
This article unearths the sexual abuse to women. Using legal approuch, this study reveals that goal of law in criminal punishment is essenstially to protect the victim from crime, especially raping. The criminal punishment to the person who commits crime is the right of the victim who has susfered from psycal aspects. Althought the goal of the law is very ideal, the implementation of the law is stiil for from ideal, since the rights of the victim os rapinf are often abandoned. This is evident if we refer to the regulations in the Criminal Punishment Law that normatively negles the protection of the vistimâs basic rights. In addition, the goal of the law in judicial (normative) subtance has not been in harmony with the substance of Islamic Law and related with the correspondence theory of truth.